Get rid of yourself: toward an aesthetics of anonymity - Eckersley, David (2019)
This thesis explores and examines the concept of anonymity by critically engaging with a set of conceptual discussions developed at the end of the 1990s as part of a larger debate regarding the changing character of the Internet. It brings these discussions into contact with a long and rich history of what the thesis calls ‘cultural anonymity’ in order to explore their theoretical and empirical limitations. It does this through the analysis of a number of historical and contemporary practices drawn from the worlds of art, literature and radical politics. The thesis demonstrates that anonymity has undergone, and continues to undergo significant mutations and transformations, insisting that any conceptual understanding of anonymity must recognise that anonymity is always produced by, and results from the material-discursive assemblages in which it is performed. It argues that far from being universally applicable and ‘value-neutral’ as some have observed, these early conceptual discussions of anonymity are premised on a decidedly liberal view of politics and subjectivity, which places limits on the analytical and political potential of the theorisations of anonymity they offer, positioning them as examples of what the thesis calls, following Deleuze and Guattari, ‘state thought’. In contrast, the thesis develops a theorisation of anonymity understood along ethico-aesthetic lines, through which anonymity is established as a concept of difference. In following these lines of inquiry, the thesis explores a politics and ethics of anonymity that is revealed as a form of refusal, which opens onto new articulations of subjectivity and the desire to remodel modes of existence. The thesis concludes by asserterting the salience of the ‘aesthetics of anonymity’ as a form of minor politics, concerned with a positive, emancipatory sense of freedom that is uncoupled from majoritarian formations and their discriminatory logics.